Design of Merchandise Inventory Accounting Information System Using Web-Based SAK ETAP Standard at Frozen Food Distribution Store - Natansya, Tyas Sylva Fitrian; Purfini, Apriani Puti (Labkat Press KA FTIK UNIKOM, 2023)
Inventory of trade goods is important in the process of buying and selling activities in a trading company, in this case it can be concluded that inventory is important for every company to supervise and manage the inventory owned. This research was conducted at the Frozen Food Distribution Store located at Rajawali Timur Street No. 68, Ciroyom, Andir, Bandung City, West Java 40182. Frozen Food Distribution Store is a trading company, selling products in the form of Frozen Food types. The method to be used in the implementation of research is the descriptive method is the process of solving problems that will be researched by describing situations that are objects or subjects. There are three data collections, namely, observation, interview and literature review. The author made the design of this application based on the website, the purpose of making this information system is expected that this system will help in carrying out daily activities in trading at the Frozen Food Distribution Store. The use of this information system is to manage inventory well with inventory cards. The results of the author's research on frozen food distribution stores do not yet have a merchandise inventory information system in which financial statements are made, the information system is made to have inventory card features to financial reporting and receive income statements every month to see profits, according to applicable accounting standards. Merchandise inventory information systems can help with weaknesses in the running system.